2016
DOI: 10.18632/oncotarget.9963
|View full text |Cite
|
Sign up to set email alerts
|

HER2-HER3 dimer quantification by FLIM-FRET predicts breast cancer metastatic relapse independently of HER2 IHC status

Abstract: Overexpression of HER2 is an important prognostic marker, and the only predictive biomarker of response to HER2-targeted therapies in invasive breast cancer. HER2-HER3 dimer has been shown to drive proliferation and tumor progression, and targeting of this dimer with pertuzumab alongside chemotherapy and trastuzumab, has shown significant clinical utility. The purpose of this study was to accurately quantify HER2-HER3 dimerisation in formalin fixed paraffin embedded (FFPE) breast cancer tissue as a novel progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 60 publications
(78 reference statements)
2
37
0
Order By: Relevance
“…This finding goes against the accepted practice of diagnosis and targeted treatment based on receptor overexpression in tumors. However, in a recent report of Weitsman et al 32 the lack of correlation between the overexpression level of HER2 and degree of HER2-HER3 dimerization as an indicator of metastatic likelihood was also shown. It has also been shown that PD-L1 expression does not accurately determine the therapeutic efficacy of anti-PD-1 drugs 33 .…”
Section: Discussionmentioning
confidence: 90%
“…This finding goes against the accepted practice of diagnosis and targeted treatment based on receptor overexpression in tumors. However, in a recent report of Weitsman et al 32 the lack of correlation between the overexpression level of HER2 and degree of HER2-HER3 dimerization as an indicator of metastatic likelihood was also shown. It has also been shown that PD-L1 expression does not accurately determine the therapeutic efficacy of anti-PD-1 drugs 33 .…”
Section: Discussionmentioning
confidence: 90%
“…This discovery has led to the invention of targeted therapies that specifically disrupt the ability of these proteins to dimerize, and with some success; e.g., a monoclonal antibody for EGFR, cetuximab, is now used alongside chemotherapy for certain colorectal and head & neck tumors, and trastuzumab is used to target HER2 in some breast cancers. We have recently published the use of FLIM/FRET to detect HER family dimerization in archived patient tissue from breast and colorectal cancer studies and clinical trials (30,35) and correlate this with the response to targeted treatment.…”
Section: Use Case I: Segmentationmentioning
confidence: 99%
“…The FRET Efficiency score is calculated for this region using the standard relationship.) B) Weka Trainable Segmentation plugin used to train the segmentation and showing a segmentation result (35). FLIMJ user interface showing a typical transient and fit from the tissue.…”
Section: Use Case I: Segmentationmentioning
confidence: 99%
“…4B; Conway et al, 2014Conway et al, , 2017Newman et al, 2011). Applications in cell proliferation (Harvey et al, 2008;Mochizuki et al, 2001), survival (Onuki et al, 2002;Tyas et al, 2000), signalling (Shih and Qi, 2017;Weitsman et al, 2016), immune cell activity (Choi and Mitchison, 2013;Li et al, 2016b), metabolism (Fehr et al, 2003;Imamura et al, 2009;Mächler et al, 2016;Okumoto et al, 2005) or migration (Seong et al, 2011;Wang et al, 2005) with a recent move to generate GEMMs of FRET biosensors for high-fidelity intravital imaging (Johnsson et al, 2014;Kamioka et al, 2012;Mukherjee et al, 2016;Nobis et al, 2017).…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 99%